Cultivo de tejidos - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1980)
Activities of the tissue culture section of the Centro Internacional de Agricultura Tropical were focused on the improvement and utilization of meristem culture methods for disease eradication (frog skin), germplasm conservation and international exchange as well as the initiation of research on other tissue culture systems (anther, protoplast cell) in cassava. (CIAT)